Reconstruction of Criminal Liability for Deepfake Misuse in Defamatory Defenses in Indonesia - Hairul Saleh Satrul; Nur Hafizal Hasanah (Civiliza Publishing, 2026)
The deepfake phenomenon as a product of artificial intelligence (AI) has created a new dimension in the crime of defamation. This research aims to analyze the deepfake phenomenon through criminological and juridical approaches to map the effectiveness of regulations in Indonesia. The method used is normative juridical research with a conceptual and case study approach. The results show that deepfake technology facilitates attacks on honor through highly realistic visual manipulation, where 96% of deepfake content on the internet is non-consensual pornography. Juridically, Article 27A of the ITE Law No. 1 of 2024 and the New Criminal Code provide a basis for enforcement, but there is still a functional legal vacuum regarding the liability of technology developers. The implications of this research emphasize the need for specific regulations (sui generis) and strengthening digital forensics to overcome evidentiary challenges in court.